Data-driven creativity for screen production students: developing and testing learning materials involving audience biometrics. Issue 2 (2nd April 2020) - Bender, Stuart; Sung, Billy
ABSTRACT: This article presents the Data-Driven Creativity Project (DDCP) materials designed to enhance screen students' understandings of how aesthetic choices impact the audience. The project first collected data on audience attention (eye-tracking), arousal (skin conductance level) and emotion (using facial expression). This data was then used in pedagogical materials delivered to two student cohorts in both lecture format and as an e-learning package. Self-reported survey data on the student experience indicates significant increase in Learning Interest toward the concepts of the DDCP, as well as strong ratings of the material's Useability and Application to Knowledge. We also report on focus group discussions of the strengths and weaknesses of the DDCP. We show that the DDCP offers an innovative and novel intervention into contemporary screen creativity pedagogy, forging a valuable teaching-research nexus between the findings of the research field of cognitive media theory and their application in the field of student production.